Molecular evidence of Leptospira interrogans sensu stricto in Cavia porcellus (guinea pig) grown for human consumption in Pasto, Nariño - Benavides-Benavides, Bibiana; Cisneros-López, Hernán Darío; Peláez-Sánchez, Ronald Guillermo (Universidad y Salud, 2021)
Introduction: Leptospirosis is an emerging zoonosis that is endemic in Colombia and affects both domestic and wild animals. It is considered an occupational risk since human transmission is associated with exposure to infected animals or environments. In the department of Nariño, the production of guinea pigs for human consumption applies traditional rearing systems that could cause animals to get infected with Leptosipira interrogans. Objective: To molecularly identify natural infection by pathogenic species of the genus Leptospira in guinea pigs used for human consumption in the municipality of Pasto (Colombia). Materials and methods: 270 kidney tissue samples were taken from guinea pigs slaughtered in two facilities. Samples were analyzed through conventional polymerase chain reaction (PCR) and Warthin Starry (W-S) differential staining. Results: While 4 (1.5%) out of the 270 samples were categorized as positive using PCR, only 1 sample showed the presence of Leptospira through W-S staining. Conclusions: Molecular techniques were useful to identify L. interrogans in kidney tissue of Cavia porcellus. Dissemination of this pathogen within this population represents an infection risk for humans and domestic animals that are in close proximity to these productive systems.